Dominant drivers of the increasing environmental footprint of changing diets in China. (20th August 2021) - Dong, Liping; Zhang, Gang; Li, Xianting; Liu, He; Pei, Huijuan; Song, Xiaoyu; Liao, Qin; Liu, Yanfei; Niu, Yibo
Abstract: Shifting diets potentially contribute significantly, both directly and indirectly, to arable land depletion, water resource shortages, and climate change. They also play a key role in the sustainable development of resources and the environment in China. However, the economic and social demographic factors driving the environmental footprints of diet are not yet well understood and quantified, which hinders an effective assessment of the potential of clean food consumption in reducing environmental stress due to resource shortages and global warming. We based this study on Chinese statistical data and considered residents in China, who account for about 20% of the world's population, as the research object to demonstrate that the environmental footprints of the residents' diets at different levels are primarily driven by Engel's coefficient and the children dependency ratio, and secondarily by the proportion of the illiterate population in the total population over six years old, and these factors have completely different mechanisms of influencing the environmental footprint of urban and rural residents. These findings provide unique evidence supporting the regulation of the diet by influencing factors that can provide a reference for policy makers globally, especially in developing countries such as China with scarce arable land and freshwater resources, to address the diet-resource environment dilemma and promote the sustainable development of humans, resources, and the environment.